Generation of stable and narrow spacing dual-wavelength ytterbium-doped fiber laser using a photonic crystal fiber - Ahmad, Harith; Salim, M.A.M.; Soltanian, M.R.K.; Azzuhri, Saaidal Razalli; Harun, Sulaiman Wadi; Yasin, Moh (Taylor & Francis, 2016)
We demonstrate the design and operation of novel narrow spacing and stable dual-wavelength fiber laser (DWFL). A 70-cm ytterbium-doped fiber has been chosen as the gain medium in a ring cavity arrangement. Our design includes a short length photonic crystal fiber, acting as a dual-wavelength stabilizer based on its birefringence coefficient and nonlinear behavior and tunable band pass filter (TBPF) to achieve narrow spacing spectrum lasing. Our laser output is considered to be highly stable, with power fluctuation less than 0.8 dB over a period of 15 min. The flexibility and tunability of TBPF, together with polarization controller enable the spacing tuning of the DWFL from 0.03 nm up to 0.07 nm for 1040 nm region, and 0.10 nm up to 0.40 nm for 1060 nm region. The tunable wavelength spacing shows the flexibility of the DWFL in addition to stable and reliable properties of fiber laser in 1-m region.